Risk Factors for Amoxicillin-Clavulanate Resistance in Community-Onset Urinary Tract Infections Caused by Escherichia coli or Klebsiella pneumoniae: The Role of Prior Exposure to Fluoroquinolones - Javier Martínez-Casanova; Silvia Gómez-Zorrilla; Nuria Prim; Agustina Dal Molin; Daniel Echeverría-Esnal; María Pilar Gracia-Arnillas; Elena Sendra; Robert Güerri-Fernández; Xavier Durán-Jordà; Eduardo Padilla; Juan Pablo Horcajada; Santiago Grau; et al. (MDPI AG, 2021)
Background: High rates of amoxicillin-clavulanate (AMC) resistance among Enterobacterales isolated from urinary tract infections (UTIs) were observed in our area. The aim of this study was to identify risk factors associated with AMC resistance in patients with community-onset UTI in emergency departments (EDs). Methods: A retrospective study was performed of all ED patients with positive urine cultures for Escherichia coli or Klebsiella pneumoniae in a Spanish tertiary-care hospital. Results: 330 urine cultures in all were included: 261 (79.1%) for E. coli and 69 (20.90%) for K. pneumonia. Rates of AMC resistance were 14.94% and 34.78%, respectively. UTI was clinically confirmed in 212 (64.24%) cases. Previous antimicrobial exposure was independently associated with AMC resistance development in E. coli and K. pneumoniae urinary isolates (OR = 2.94, 95% CI = 1.55-5.58). Analyses of infected patients revealed that previous exposure to fluoroquinolones (OR = 3.33, 95% CI = 1.10-10.12, p = 0.034) and to AMC (OR = 5.68, 95% CI = 1.97-16.44, p = 0.001) was significantly associated with isolation of AMC-resistant strains. Conclusions: Prior antibiotic exposure, particularly to AMC or fluoroquinolones, was the only independent risk factor associated with development of AMC resistance in E. coli and K. pneumoniae urinary isolates from patients attending the ED.